BOC is a modifier gene in holoprosencephaly. Issue 11 (21st July 2017) - Hong, Mingi; Srivastava, Kshitij; Kim, Sungjin; Allen, Benjamin L.; Leahy, Daniel J.; Hu, Ping; Roessler, Erich; Krauss, Robert S.; Muenke, Maximilian
Abstract: Holoprosencephaly (HPE), a common developmental defect of the forebrain and midface, has a complex etiology. Heterozygous, loss‐of‐function mutations in the sonic hedgehog (SHH) pathway are associated with HPE. However, mutation carriers display highly variable clinical presentation, leading to an "autosomal dominant with modifier" model, in which the penetrance and expressivity of a predisposing mutation is graded by genetic or environmental modifiers. Such modifiers have not been identified. Boc encodes a SHH coreceptor and is a silent HPE modifier gene in mice. Here, we report the identification of missense BOC variants in HPE patients. Consistent with these alleles functioning as HPE modifiers, individual variant BOC proteins had either loss‐ or gain‐of‐function properties in cell‐based SHH signaling assays. Therefore, in addition to heterozygous loss‐of‐function mutations in specific SHH pathway genes and an ill‐defined environmental component, our findings identify a third variable in HPE: low‐frequency modifier genes, BOC being the first identified. Abstract : Holoprosencephaly (HPE), the most developmental common defect of the forebrain, is best explained by a "mutation with modifier" model. However, HPE modifier genes have not been identified. Here, we report HPE‐associated missense variants within the Hedgehog coreceptor BOC (arrows). Functional analyses of these variants, along with previous work in mouse models, are consistent with the conclusion that these variants act as phenotypic modifiers of a driver mutation or environmental insult.